1995
DOI: 10.1007/bf00179972
|View full text |Cite
|
Sign up to set email alerts
|

Flexibility and alignment of the cervical spine after laminoplasty for spondylotic myelopathy

Abstract: The long term effects of laminoplasty on cervical movement and alignment were investigated by radiography and CTscans in a study of 56 patients with multisegmental myelopathy who had undergone a C3 to C7 open-door laminoplasty. Follow up averaged 5.8 years. Satisfactory neurological improvement occurred in 73%. Cervical flexion decreased by 35% and extension by 57%; the decrease of both movements was statistically significant. Decreased vertebral slip, as well as slightly reduced lordosis, was seen after opera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
55
0
1

Year Published

1996
1996
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(56 citation statements)
references
References 16 publications
0
55
0
1
Order By: Relevance
“…In two recent studies from our group, insigni®cant reduction of lordosis was noted after laminoplasty. 14,24 Although this reduction in the lordotic alignment of the postoperative cervical spine did not signi®cantly a ect neurological improvement, biomechanically, it may be inconvenient for the cord to be released from the lesions at posterior vertebral rims. By evaluating the spinal canal using a threedimensional approach, the present series showed that reductions of lordosis were associated with reduced volume of the cervical spinal canal postoperatively.…”
Section: Discussionmentioning
confidence: 94%
“…In two recent studies from our group, insigni®cant reduction of lordosis was noted after laminoplasty. 14,24 Although this reduction in the lordotic alignment of the postoperative cervical spine did not signi®cantly a ect neurological improvement, biomechanically, it may be inconvenient for the cord to be released from the lesions at posterior vertebral rims. By evaluating the spinal canal using a threedimensional approach, the present series showed that reductions of lordosis were associated with reduced volume of the cervical spinal canal postoperatively.…”
Section: Discussionmentioning
confidence: 94%
“…Although there were many reports of good postoperative neurological improvements after laminoplasty for cervical myelopathy [12,23,28], several postoperative problems have also been reported, including late deterioration of myelopathy symptoms [9,15,20,23], C5 root palsies [3,16,17,21,28], axial symptoms [7,11,14,24,25,31], cervical malalignment [8,15,26,28,30] and loss of flexion-extension ROM [1,5,6,13,15,22,26,28,30]. Especially in recent years, a great deal of attention has been paid to axial symptoms as postoperative complications which adversely affect patients' quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…Chiba et al reported that several patients obtained an acceptable clinical outcome after LP alone, even in the context of cervical kyphosis, and they speculated that the slack of the spinal cord, especially in patients showing reduction of multilevel disc height, should allow acceptable recovery [2]. On the other hand, several authors have insisted that the outcome of LP alone for CSM with local kyphosis was not acceptable [3,4]. Baba et al [3] reported that patients with preoperative kyphosis (mean of 11.7°) showed significantly poorer neurological improvement.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, several authors have insisted that the outcome of LP alone for CSM with local kyphosis was not acceptable [3,4]. Baba et al [3] reported that patients with preoperative kyphosis (mean of 11.7°) showed significantly poorer neurological improvement. Suda et al [4] also reported that outcomes of LP for CSM accompanying local kyphosis with an angle exceeding 13°(when coexisted with myelomalacia) and 5°(without myelomalacia) were poorer than those for CSM without local kyphosis in their multivariate logistic regression analysis.…”
Section: Introductionmentioning
confidence: 99%